Pengaruh Lingkungan Kerja Fisik, Pengawasan dan Kompetensi terhadap Kinerja Pegawai Non ASN pada Dinas Kebudayaan Kabupaten Tabanan - Ariningsih, Ni Putu Yunita; Yudy Wijaya, Putu; Ary Pratiwi, Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The success of an institution or company really depends on the abilities and skills of employees in running these work units. The aim of this research is to determine the influence of the physical work environment, supervision and competence on the performance of non-ASN employees at the Tabanan Regency Culture Service. In this research, the samples used were 40 non-ASN employees at the Tabanan Regency Culture Service. Through a questionnaire, data was collected on a scale of 1-5. After analyzing using regression analysis, it can be concluded that the physical work environment, supervision and partial or simultaneous competence on the performance of non-ASN employees at the Tabanan Regency Culture Service are positive and significant. For future researchers, researchers have suggestions to try examining other variables besides those already studied, such as human relations, job rotation, or seniority level. It is possible that this can also affect employee performance, don't forget to try using other factors, increase the number of samples, and look for different research locations so that the results are stronger.